“The rural issue is complicated”: Trade unions and spatial organization in the paddy fields of eastern Uruguay. - Frank Gabin, Nicolas Esteban (PEGADA - A Revista da Geografia do Trabalho, 2023)
In studies on rural salaried workers' unions in Uruguay, several authors have identified the incidence of factors attributable to spatial organization in the emergence and permanence of organizations, factors that remain unexplored. Analyzing empirical and bibliographical evidence on the rice complex in Eastern Uruguay, I identify eleven ways in which spatial organization conditions (as a stimulus or constraint) rural union activity in the sector. I conclude that studying how trade union organizations and their adversaries make use of spatial organization is a promising way to understand organizational dynamics.